Merry and bright [compact disc, unabridged] : a novel - Macomber, Debbie (Random House Audio, 2017)
Between her full-time job and taking care of her family, it's been a long year for Merry, and her social life has all but disappeared. Trying to get her to take a break from the responsibilities of everyday life, her mother and brother make her an online dating profile, and the matches start rolling in. Intrigued by their similar interests, she starts chatting with a charming stranger, and their exchanges soon become the brightest part of her day. But everything turns upside down when they finally meet in person.